DETERMINAN PENCEGAHAN KECURANGAN DALAM ALOKASI DANA DESA - Falisa, Devina Dian; Aprianti, Siska; Sarikadarwati (Jurnal Riset Terapan Akuntansi, 2025)
This study aims to examine the extent to which village apparatus competence, employee morality, internal control systems, and organizational culture influence fraud prevention efforts in the management of village funds in Gunung Megang District, Muara Enim Regency, covering 13 villages in 2025. The sampling was conducted using a saturated sampling technique, while the primary data were collected through questionnaires. Data analysis was performed using multiple linear regression with the assistance of SPSS version 26. The research findings indicate that, partially, village apparatus competence and internal control systems have a significant negative effect on fraud prevention, whereas apparatus morality and organizational culture have a significant positive effect. Simultaneously, these four variables together contribute a significant positive impact of 69.9% toward fraud prevention in the management of village funds. Keywords: prevention of village fund management fraud, the competence of village apparatus, the morality of the apparatus, internal control systems, organizational culture.